AKTIVITAS SITOTOKSIK EKSTRAK ETANOLIK DAN FRAKSI DARI EKSTRAK ETANOLIK DAUN PANDAN (Pandanus amaryllifolius ROXB) TERHADAP SEL KANKER PAYUDARA MCF-7 - Nur Ismiyati; Ana Mardiyaningsing; Trilestari - (Universitas Muhammadiyah Semarang, 2015)
Breast cancer is the second leading cause of cancer death among women in the world. To overcome the high incidence of cancer, the discovery and development of cancer treatments continues to be pursued. Pandan leaf (Pandanus amaryllifolius Roxb) is one of natural product that had cytotoxic activity. This study investigated the cytotoxic activity on MCF-7 breast cancer cells and to identify the chemical subtance groups of pandan leaves ethanol extract and fractions as chemopreventive agent. Active contents of pandan leaves was extracted by remaceration with 70% ethanol. Variation solvent of the water, chloroform, and ethyl acetate used to fractionation of pandan leaf ethanolic extract. Qualitative test were done to identify the chemical substances of pandan leaves etanolic extracts and fractions. Cytotoxic activity of sample was measured using MTT assay. The result of the phytochemical screening showed that the etanolic extract and water fractions of pandan leaf contained alcaloids, poliphenol and saponin. Chloroform fractions contained alcaloids and poliphenol. Pandan leaves ethanol extracts and chloroform fractions showed cytotoxic activity on MCF-7 cell line with IC50 of 540 μg/ml and 160 μg/ml whereas ethyl acetate fractions and water fractions of pandan leaves showed no cytotoxic activity on MCF-7 cell line.Keywords: Pandanus amaryllifolius Roxb, MCF-7 cell line, cytotoxic activity, etanolic extract,fractionation